Podocan-like Protein: A novel small leucine-rich repeat matrix protein in bone - Mochida, Yoshiyuki (2011)
Recently, significant attention has been drawn to the biology of small leucine-rich repeat proteoglycans (SLRPs) due to their multiple functionalities in various cell types and tissues. Here, we characterize a novel SLRP member, “Podocan-like (Podnl) protein” identified by a bioinformatics approach. The Podnl protein has a signal peptide, a unique cysteine-rich N-terminal cluster, 21 leucine-rich repeat (LRR) motifs, and 1 putative N-glycosylation site. This protein is structurally similar to podocan in SLRPs. The gene was highly expressed in mineralized tissues and in osteoblastic cells and the high expression level was observed at and after matrix mineralization in vitro. Podnl was enriched in newly formed bones based on immunohistochemical analysis. When Podnl was transfected into osteoblastic cells, the protein with N-glycosylation was detected mainly in the cultured medium, indicating that Podnl is a secreted N-glycosylated protein. The endogenous Podnl protein was also present in bone matrix. These data provide a new insight into our understanding of the emerging SLRP functions in bone formation.